2014
DOI: 10.1016/j.fertnstert.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work and life stress on semen quality

Abstract: Objective To evaluate associations between work-related stress, stressful life events, and perceived stress and semen quality. Design Cross-sectional analysis. Setting Northern California. Patient(s) 193 men from the Child Health and Development Studies evaluated between 2005–2008. Intervention(s) None. Main Outcome Measure(s) Measures of stress including job strain, perceived stress, and stressful life events; outcome measures of sperm concentration, percentage of motile sperm, and percentage of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 27 publications
2
59
2
5
Order By: Relevance
“…This on-going surveillance facilitated our ability to locate cohort members at midlife (Susser et al, 2011, Cirillo et al, 2011; Terry et al, 2011; Janevic et al, 2014). Efforts to maintain information about the location of cohort families, the rich data on a relatively large subgroup through adolescence, and sufficient variation in race and SES (see online supplement) make the cohort a strong setting for studying the emergence of health disparities.…”
Section: The Child Health and Development Studies Cohortmentioning
confidence: 99%
“…This on-going surveillance facilitated our ability to locate cohort members at midlife (Susser et al, 2011, Cirillo et al, 2011; Terry et al, 2011; Janevic et al, 2014). Efforts to maintain information about the location of cohort families, the rich data on a relatively large subgroup through adolescence, and sufficient variation in race and SES (see online supplement) make the cohort a strong setting for studying the emergence of health disparities.…”
Section: The Child Health and Development Studies Cohortmentioning
confidence: 99%
“…Infertile men experience infertilityspecific anxiety and socially isolated men are more vulnerable to severe anxiety (Fisher & Hammarberg, 2011). Researchers from the USA identified life stress as a factor in reducing men's fertility; however, job strain had no effect on the sperm parameters (Janevic et al, 2014). A study of Danish men found that increased stress reduced all sperm parameters (Nordkap et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although reproductive abnormalities in the male partner are identified in about one-half of these cases, few risk factors for abnormal semen quality have been identified (Juul et al, 1999;Kovac et al, 2013). Emerging evidence suggests that lifestyle factors such as smoking (Ramlau-Hansen et al, 2007;Wegner et al, 2010), diet (Afeiche et al, 2014), physical activity (Hajizadeh Maleki et al, 2013;Vaamonde et al, 2006;Wise et al, 2011), overweight and obesity (Crujeiras and Casanueva, 2014;Sermondade et al, 2013), stress (Janevic et al, 2014), and sexual activity habits among others seem to have a cumulative effect on sperm quality (Wogatzky et al, 2012). Physical activity is an efficient method for preventing weight gain, and has a broad and positive systemic influence, such as reducing the risk for cardiovascular diseases, stroke, type 2-diabetes, cancer and metabolic syndrome (US department of Hyealth and Human Services, 2008), and could therefore be potentially related to sperm quality.…”
Section: Introductionmentioning
confidence: 99%